1996
DOI: 10.1007/bf01816437
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder motility in systemic sclerosis

Abstract: In 20 patients with systemic sclerosis (SSc) and 24 healthy controls, gallbladder motility was evaluated by abdominal ultrasonography after stimulation by a standard liquid meal. Results from patients with normal and disturbed oesophageal function were analysed separately in order to investigate the significance of gallbladder motility as a parameter for gastrointestinal involvement in SSc. All patients showed a marked decrease in gallbladder size after stimulation (patients 61 +/- 13%; controls 48 +/- 12%). P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…Regarding cholelithiasis, it was significantly lower in SSc patients compared to controls. Two studies in the literature showed that gallbladder motility in patients with SSc was not significantly reduced when compared to controls [ 21 , 22 ], consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding cholelithiasis, it was significantly lower in SSc patients compared to controls. Two studies in the literature showed that gallbladder motility in patients with SSc was not significantly reduced when compared to controls [ 21 , 22 ], consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%